Analysis of User Views of the Climate Information System in Indonesia - Faradiba Faradiba; Hadi Saputra (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Climate information is important in decision making. Access to relevant and timely weather information is an important factor in increasing farmers' resilience to climate change. Information systems are considered essential for enhancing the ability of individuals, businesses and governments to adapt to change and climate change. Information users can use the information system to assist in making decisions about management adjustments to climate projections. Climate information should be communicated in languages understood by local farmers and linked directly to farm management decision-making processes to ensure information is timely and usable by small producers. The survey was conducted on the user's level of trust in the climate information system issued by the BMKG. No less than 59 respondents stated that the climate information obtained was very good, accurate and timely, received late, difficult to understand, diverse climate information did not reach all sectors. In order to remain productive in running the agricultural industry, accurate information is needed so that users can make optimal use of it. By knowing climate information, climate risks can be minimized.